Sky luminance distribution model based on the information method and ant colony system. (August 2022) - He, Y; Zhang, X; Quan, L; Shi, D; Zhang, Y
This study presents a novel model to estimate the sky luminance distribution (SLD) using the information method based on the research results of the SLD and atmospheric optics theory. The ant colony system of complex optimisation heuristic algorithms is used to analyse and optimise the influencing factors of sky luminance. The SLD using the information method is universal and is not related to geographical, latitudinal or climatic conditions. First, a simple and clear sky classification method is proposed. Then, a model framework is constructed. Using the ant colony system, the effects of the sky luminance elements are analysed and optimised, and numerical expressions for the coefficients of the relative luminance distribution are obtained. Finally, the proposed model is compared with other sky models (Perez's model, the Commission Internationale de l'Eclairage model and Igawa's all-sky model). The results show that the proposed model offers significant advantages for generating a universal SLD. Moreover, the information method SLD model can significantly enrich the coverage of the reference sky, and it avoids the shortcomings of existing sky models.